Statin Use and Aneurysm Risk in Patients With Bicuspid Aortic Valve Disease. Issue 1 (22nd December 2015) - Taylor, Alexander P.; Yadlapati, Ajay; Andrei, Adin‐Cristian; Li, Zhi; Clennon, Colleen; McCarthy, Patrick M.; Thomas, James D.; Malaisrie, S. Chris; Stone, Neil J.; Bonow, Robert O.; Fedak, Paul W.M.; Puthumana, Jyothy J.
ABSTRACT: Background: No medical therapy has been proven to prevent the progression of aortic dilatation in bicuspid aortic valve (BAV) disease, and prophylactic aortic surgery remains the mainstay of treatment. Hypothesis: Among patients with BAV disease who are referred for surgery, preoperative statin use is associated with decreased odds of ascending aortic dilatation. Methods: We reviewed all BAV patients who underwent aortic valve and/or aortic surgery at our center between April 2004 and December 2013. Aortic diameter (AD), defined as the maximum ascending aortic dimension, was determined by magnetic resonance imaging, computed tomography, or echocardiography. Patients were divided into 2 groups: maximal AD <4.5 cm or ≥4.5 cm. The association between preoperative statin use and aortic dilatation was assessed using multivariable logistic regression modeling. Results: Of 680 consecutive patients, 405 (60%) had AD <4.5 cm (mean age, 60 ± 14 years; 45% on statins), whereas 275 (40%) had AD ≥4.5 cm (mean age, 54 ± 13 years; 35% on statins) at the time of surgery. After adjusting for age, body surface area, sex, hypertension, aortic stenosis, severity of aortic regurgitation, and use of angiotensin‐converting enzyme inhibitors, angiotensin receptor blockers, and β‐blockers, patients with AD ≥4.5 cm had 0.66× lower odds (95% confidence interval: 0.45‐0.96) of being on preoperative statins compared with those with AD <4.5 cm ( P = 0.029). Conclusions: In a retrospective study of BAV patients referred for surgery, preoperative statin use was associated with lower odds of clinically significant ascending aortic dilatation.